Performance-related affective experiences in elite shooters during the preparation season - Lima Fogaça, Janaina; Päkk, Robert (2012)
Janaina Lima Fogaca & Robert Päkk, 2012. Performance-related affective experiences in elite shooters during the preparation season. Department of Sport Sciences. University of Jyväskylä. 79 p. The present study examined affective experiences in elite shooters using two types of profiles developed within the Individual Zones of Optimal Functioning (IZOF) model, namely traditional IZOF and probabilistic estimation of IZOF. The Emotional State Profile (ESP-40; Hanin, 2010) assessed four categories of emotion, namely positively- toned functionally optimal emotions, positively-toned dysfunctional emotions, negatively-toned functionally optimal emotions, and negatively-toned dysfunctional emotions. Its data was used to develop traditional IZOF profiles. The affect grid (AG; Russell, Weiss, & Mendelsohn, 1989) measured two affective dimensions, namely pleasantness and arousal, and its data was used to develop probabilistic estimation profiles. Thus, this exploratory study aimed at exploring affective performance-related experiences of elite skeet shooters. It examined the validity of recalled optimal and dysfunctional emotions in the prediction of performance. Furthermore, logistic regression was used to estimate probability of performance based on pre-performance affective data. The participants were three male elite Olympic Skeet shooters from the Finnish National Skeet Shooting Team. First, the IZOF profiles were developed using the ESP- 40, based on recalled best and worst performances. Assessment of actual emotions and affect were carried out during three training camps organized within a three-month period. Specifically, shooters’ emotions were assessed 30 min prior to performance using ESP-40 and affect was assessed 10 min prior to performance using AG. Feedback about individual profiles was given to the athletes to enable their evaluation of the use of the instruments, and usefulness and accuracy of the profiles for their practice. This evaluation was carried out through two 7-point Likert scale sets of questions. Results indicated that the participants’ emotional and affective performance-related dynamics during the training camps were mostly within the predicted zones of optimal functioning according to the IZOF and probabilistic estimation profiles, respectively. A positive relationship between the intensity of emotions in ESP-40 and affect in AG was found. This study provides important information about assessment of emotions and affect in elite individual sports. It demonstrates two successful and practical approaches of profiling athletes’ emotions and affect, predicting their future performance, and providing useful practical feedback to improve their psychological preparation. Future studies should investigate further the relationship between emotion and affect assessed via IZOF-based instruments and AG, respectively.